Reimagining Open Textbooks Through a Decolonising Lens: Non-Linear Practices for Holistically Integrating First Nations Knowledges into Curriculum - Shirley Godwin; Andrew Buldt; Steven Chang; Sebastian Kainey; Wendy Ratcliffe; Vivian Luker; Melissa Digiacomo; Emerson Taylor (2025)
This case study describes our project to transform an undergraduate open textbook at La Trobe University . At the time of writing this case study the revised version of the text is forthcoming. Here we share one of our key outcomes: the collaborative process we are using to make the transformative revisions. We reflect on a First Nations-led cultural safety review process that is enabling health science academics and library staff to jointly reconstitute this Open Education Resource (OER) as a culturally responsive text that is inclusive and accessible for diverse learners. We highlight the role of First Nations staff in leading a decolonising agenda and how non-Indigenous practitioners are supporting them through culturally responsive practices. We focus on how the project embodies First Nations ways of knowing, being, and doing through Third Spaces that foster power equity and mutually beneficial two-way learning. These ways of working provide an active alternative to the emotionally based paralysis that commonly affects non-Indigenous people, stemming from a fear of “doing the wrong thing”. This often demobilises their capacity to transform beyond allyship on an individual level (which can be tokenistic or performative and a way to stay comfortable) into ‘accomplices’ striving for wider systemic change, regardless of personal or professional discomfort (Finlay, 2020; Rix et al., 2023). Our approach is part of a broader paradigm shift to integrate First Nations knowledges into higher education curriculum in a meaningful way that is holistic rather than tokenistically additive. This paradigm shift reflects a decolonising approach which requires de-centreing dominant Western perspectives by challenging deeply rooted conventional norms and principles, and re-positioning colonial power in collaborative relationships (Smith, et al., 2018). We conclude our case study with some final reflections as prompts for practitioners to use for normalising culturally responsive practices in the Australian open education ...